2009
DOI: 10.1038/nm.2033
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the c-Abl–TAp63 pathway protects mouse oocytes from chemotherapy-induced death

Abstract: Germ cells are sensitive to genotoxins, and ovarian failure and infertility are major side effects of chemotherapy in young patients with cancer. Here we describe the c-Abl-TAp63 pathway activated by chemotherapeutic DNA-damaging drugs in model human cell lines and in mouse oocytes and its role in cell death. In cell lines, upon cisplatin treatment, c-Abl phosphorylates TAp63 on specific tyrosine residues. Such modifications affect p63 stability and induce a p63-dependent activation of proapoptotic promoters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
349
2
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 325 publications
(372 citation statements)
references
References 34 publications
14
349
2
7
Order By: Relevance
“…29 In response to genotoxic stress, TAp63 is phosphorylated by cAbl and induces apoptosis of oocytes, having a crucial role in genome protection of the female germ-line. 29,30 A more recent study established a function of TAp63 in mediating Ras-induced senescence and preventing tumorigenesis in vivo, in a model of p53-nullizygous mice. 20 In addition, TAp63 has a crucial role in preventing invasiveness and metastasis of epithelial tumors by controlling expression of a crucial set of metastasisinhibitor genes.…”
Section: Tap73 α αmentioning
confidence: 99%
“…29 In response to genotoxic stress, TAp63 is phosphorylated by cAbl and induces apoptosis of oocytes, having a crucial role in genome protection of the female germ-line. 29,30 A more recent study established a function of TAp63 in mediating Ras-induced senescence and preventing tumorigenesis in vivo, in a model of p53-nullizygous mice. 20 In addition, TAp63 has a crucial role in preventing invasiveness and metastasis of epithelial tumors by controlling expression of a crucial set of metastasisinhibitor genes.…”
Section: Tap73 α αmentioning
confidence: 99%
“…p73Y99-p YAPY357-p Figure 1 In late response to DNA damage, c-Abl is activated leading to phosphorylation and activation of p73 (p73Y99-p) [8][9][10] and YAP (YAPY357-p) 12 resulting in cell apoptosis. Reuven et al 1 demonstrate that upon exposure of dense cells to ionizing radiation, activated LATS2 phosphorylates c-Abl, hence inhibiting its kinase function and resulting in reduced p73Y99-p and YAPY357-p-mediated apoptosis leading to cytoprotection.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…A central protein that has been widely associated with various aspects of the DDR is the non-receptor tyrosine (Y) kinase c-Abl (ABL1). [7][8][9] Upon exposure to g-irradiation, c-Abl undergoes robust activation leading to phosphorylation of target substrates including p73, 7-9 p63, 10 YAP, 11 and MDM2. 12 c-Abl mediated the phosphorylation of p73 at Y99 and of YAP at Y357 is associated with enhanced apoptosis upon DNA damage, thus implying a tumor suppressive function of YAP.…”
mentioning
confidence: 99%
“…It has been proposed that, following DNA damage in oocytes, TAp63 becomes activated through phosphorylation by c-Abl tyrosine kinase (Gonfloni et al, 2009). Gonfloni and colleagues have shown that c-Abl inhibition by imatinib or GNF-2 protected oocytes from apoptosis in response to cisplatin-induced DNA damage (Gonfloni et al, 2009;Maiani et al, 2012).…”
Section: P63-dependent Pathwaymentioning
confidence: 99%
“…Gonfloni and colleagues have shown that c-Abl inhibition by imatinib or GNF-2 protected oocytes from apoptosis in response to cisplatin-induced DNA damage (Gonfloni et al, 2009;Maiani et al, 2012). p63 phosphorylation drives resting inactive dimmers to form tetramers which possess the ability to bind DNA and activate the transcription machinery (Deutsch et al, 2011).…”
Section: P63-dependent Pathwaymentioning
confidence: 99%